2011
DOI: 10.1016/j.cej.2010.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO removal over Au/CeFe and CeCu catalysts in microreactors studied through kinetic analysis and CFD simulations

Abstract: Selective CO removal over Au/CeFe and CeCu catalysts in microreactors studied through kinetic analysis and CFD simulations, Chemical Engineering Journal (2010), doi:10.1016/j.cej.2010.08.083 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 38 publications
5
32
0
1
Order By: Relevance
“…8) and the R-WGS reactions (Eq. 9) with the gold catalyst, it was observed that the rate equations developed for the CeCu solid [36] remained valid. For obtaining a good description of the experimental data the rate expression for the CO oxidation over AuCeCu must include some adsorption terms (Eq.…”
Section: Catalytic Performance and Kinetic Modelmentioning
confidence: 98%
See 4 more Smart Citations
“…8) and the R-WGS reactions (Eq. 9) with the gold catalyst, it was observed that the rate equations developed for the CeCu solid [36] remained valid. For obtaining a good description of the experimental data the rate expression for the CO oxidation over AuCeCu must include some adsorption terms (Eq.…”
Section: Catalytic Performance and Kinetic Modelmentioning
confidence: 98%
“…It is intended this way comparing the CO oxidation performance of the catalysts under different O 2 availability conditions which can be interesting to better understand the PROX reaction in the presence of these solids and design more efficient catalysts. Additionally, a kinetic model is formulated for the Au-CuO x /CeO 2 catalyst in the PROX reaction and compared to that for the CuO x /CeO 2 solid that was reported in a previous study [36].…”
Section:  mentioning
confidence: 99%
See 3 more Smart Citations